The works of the visual image and its relationship to technical presentation methods In the products of art education students (Journal of the College of Basic Education, 2024)
The current research aims to identify the uses of the visual image and its relationship to methods of technical display in the productions The research population of art education students consisted of (10) works of plastic arts and (3) works of art were selected as the sample for analysis. The researcher used a descriptive approach (content analysis method) compatible with the objectives of the study, prepared a research tool consisting of an analysis form, and used statistical methods: the Cooper equation to obtain inter-arbitrator agreement, the Scott equation to calculate tool validity, and the split-half method to extract reliability Pearson correlation coefficient was used. Most important results: Methods of technical presentation of artistic production are achieved by adopting artistic treatments that rely on a field of signs, signs, and display of elements, which accept various dimensions of interpretation and are capable of producing an ever-changing visual vision linked to the student’s artistic taste, which reshapes its meanings using different techniques or materials. The most important conclusions: The visual image carries many different symbolic and intellectual connotations and conveys various messages with specific symbols that are difficult to understand, analyze and decipher except through technical expertise.